2023
DOI: 10.1039/d3qo01482g
|View full text |Cite
|
Sign up to set email alerts
|

Radical cascade cyclization of 1,n-enynes under photo/electrochemical conditions

Zhenzhi Cai,
Sven Trienes,
Kairui Liu
et al.

Abstract: During the past decade, photo- and electrochemical reactions proceeding via single-electron-transfer (SET) triggered radical pathways have emerged as an indispensable strategy for the efficient formation of chemical bonds. Especially, radical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 84 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…9 Very recently, the groups of Studer/Xuan, and Zhang separately summarized a wide range of efficient cyclization reactions of 1, n -enynes reported by numerous researchers, which result in various heterocycles. 10 Meanwhile, Li et al reported a radical bicyclization of 1,7-enynes with tert -butyl nitrite to access nitro-containing pyrrolo[4,3,2- de ]quinolinones. 11 Wei and coworkers developed a radical bicyclization of 1,6-enynes with sulfonyl hydrazides to result in sulfone-featured polyheterocycles.…”
mentioning
confidence: 99%
“…9 Very recently, the groups of Studer/Xuan, and Zhang separately summarized a wide range of efficient cyclization reactions of 1, n -enynes reported by numerous researchers, which result in various heterocycles. 10 Meanwhile, Li et al reported a radical bicyclization of 1,7-enynes with tert -butyl nitrite to access nitro-containing pyrrolo[4,3,2- de ]quinolinones. 11 Wei and coworkers developed a radical bicyclization of 1,6-enynes with sulfonyl hydrazides to result in sulfone-featured polyheterocycles.…”
mentioning
confidence: 99%